Education on John Dewey’s Pragmatism (Critical Analysis Study of John Dewey's View on Education) - Alif Cahya Setiyadi; Fuad L Anshori; ⁠Moh. Ilham Fahreza (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the concept of John Dewey's Pragmatism Education. As far as the author reads, John Dewey's Education is oriented towards Pragmatism by carrying out the concepts of "Learning by Doing" and Progressive Education. Dewey's educational reform was motivated by his passion for traditional dogmatic and authoritarian approaches to education. In the preparation of this article, the author uses the Library Research method by analyzing the concept of Dewey's thoughts from his works so that it becomes a complete concept. The results of this study have at least two important points, first, John Dewey's Pragmatism Education Concept emphasizes the urgency of experience for students to become provisions in community life. Second, Dewey's concept of education is considered to still have confusion from its method, substance, and axiology, so some Western scientists to Muslims criticize the concept.